If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + -2x) + 8 = 15 (1 * 5 + -2x * 5) + 8 = 15 (5 + -10x) + 8 = 15 Reorder the terms: 5 + 8 + -10x = 15 Combine like terms: 5 + 8 = 13 13 + -10x = 15 Solving 13 + -10x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -10x = 15 + -13 Combine like terms: 13 + -13 = 0 0 + -10x = 15 + -13 -10x = 15 + -13 Combine like terms: 15 + -13 = 2 -10x = 2 Divide each side by '-10'. x = -0.2 Simplifying x = -0.2
| 6(x-3)-2(x-2)=1 | | 23=33-2(4-2w) | | 12/11•5/8 | | 12/8•5/8 | | 7(3x-2)=-39 | | -9x+3=-8x | | 9x+8=-1x-13 | | 3+.20y=2x+4 | | (n+18)+2n=90 | | -23=2x+3x+2 | | x/3-3=-2 | | 6(x/6)-6(4)=6(x/6) | | -17x+18=13 | | x-7=1-9 | | -7=5-2n+6n | | a+(a-15)=55 | | -8-n=0 | | 8p+3=3p+13 | | 5n+3=14-5n | | -2x+5-5x=5 | | 68mi/h=mi/sec | | (-14xy^2)/(21y^3)= | | 8x-(3x-11)=36 | | 4y=2x+9solve | | 3b^2+7b-6= | | 0.4x-8=9-0.6x | | -5=6x-4x+1 | | 72+6y=-6y | | 5x^2-2x-365=0 | | 40x+8y=48 | | 4p+7=3p+11 | | (5y-4z)(7y+3z)= |